Olmsted, Challenging The Secret Government; The Post-Watergate Investigations Of The CIA And FBI - Merriam, Scott (Teaching History: A Journal of Methods, 1997)
Almost immediately after Watergate, the news broke that the CIA and FBI had been guilty of huge abuses of power both in the United States and abroad. The media, Congress, and the White House all promised investigations. However, contrary to popular expectations, the inquiries were stymied. The end result, Olmsted argues, was that neither Congress nor the press pushed for changes, or challenged the executive branch, in the oversight of the intelligence community.